OPTIMIZING GLOBAL COST-TO-SERVE THROUGH ROBOTICS AND DIGITAL SMART FACTORIES: A MULTI-PLANT MANUFACTURING MODEL - Kamalendar Reddy Kotha; Phanindra Kalva; Shishir Biyyala (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article examines the optimization of global cost-to-serve in manufacturing through the implementation of robotics and digital smart factories. In the context of Industry 4.0, we present a comprehensive framework for multinational manufacturers to leverage advanced technologies across their global plant networks. Our research, based on extensive literature review and empirical data from multiple countries, addresses key considerations including technology selection, implementation strategies, workforce development, and network optimization. The article reveals significant benefits, including an average 30% reduction in labor costs, 25% increase in overall equipment effectiveness, and 18% reduction in overall cost-to-serve. However, challenges such as high initial investment, workforce reskilling, and technology integration complexities are also identified. The proposed decision-making framework guides manufacturers through assessment, technology mapping, cost-benefit analysis, implementation planning, network optimization, and continuous monitoring stages. This article provides valuable insights for manufacturing companies seeking to enhance their global competitiveness through the strategic adoption of Industry 4.0 technologies.